Efficacy of Renin-angiotensin-aldosterone-system inhibitors for heart failure with preserved ejection fraction and left ventricular hypertrophy -from the KUNIUMI Registry Acute Cohort-. Issue 6 (June 2022) - Odajima, Susumu; Tanaka, Hidekazu; Fujimoto, Wataru; Kuroda, Koji; Yamashita, Soichiro; Imanishi, Junichi; Iwasaki, Masamichi; Todoroki, Takashi; Okuda, Masanori; Hayashi, Takatoshi; Konishi, Akihide; Shinohara, Masakazu; et al.
Highlights: RAAS (renin-angiotensin-aldosterone-system) inhibitors tended to have favorable outcomes in HFpEF (heart failure with preserved ejection fraction) with LVH (left ventricular hypertrophy). RAAS inhibitors were not associated with outcomes in HFpEF without LVH. RAAS inhibitors had favorable outcomes in HFpEF with LVH and mild-moderate CKD (chronic kidney disease). RAAS inhibitors were not associated with outcomes in HFpEF with LVH and severe CKD. HFpEF phenogrouping is important to identify effective pharmacological treatments. Abstract: Background: Heterogeneity of heart failure (HF) with preserved ejection fraction (HFpEF) would contribute to the difficulty in identifying effective treatments, and interest in the phenogrouping of HFpEF as a potential means for predicting patients who respond to cardioprotective drugs has been increasing. Methods: We studied 468 first-hospitalized HFpEF patients among 1971 acute-hospitalized HF patients from KUNIUMI Registry Acute Cohort. The primary endpoint was defined as HF-rehospitalization and cardiovascular death over a median follow-up period of 508 days. Results: In HFpEF patients with left ventricular hypertrophy (LVH), patients prescribed renin-angiotensin-aldosterone-system (RAAS) inhibitors had similar outcomes compared to those without (HR, 0.77; 95% CI 0.51-1.16; p  = 0.21), and the outcome was also similar between patients with and without RAAS inhibitors' prescription in HFpEF patients without LVH. Moreover, in HFpEF patients with LVH and mild-moderate chronic kidney disease (CKD), which was determined as an estimated glomerular filtration rate (eGFR) of 30-60 mL/min/1.73 m 2, patients prescribed RAAS inhibitors had significantly favorable outcomes compared to those without (HR 0.39; 95% CI 0.19-0.80; p =  0.01). In HFpEF patients with LVH and severe CKD, which was defined as eGFR <30 mL/min/1.73 m 2, the outcome was similar between patients with and without RAAS inhibitor prescription. Multivariable Cox regression analysis showed that the prescription of RAAS inhibitors was the only independent predictor of outcome in HFpEF patients with LVH and mild-moderate CKD (HR 0.49; 95% CI 0.25–0.94; p =  0.03). Conclusions: Our findings showed the importance of HFpEF phenogrouping for identifying effective pharmacological treatments. Graphical Abstract: Image, graphical abstract